Antimicrobial effectiveness of adhesive systems. An effective alternative: literature review - Encarnación, Wilson (2023)
Adhesive systems are used in daily clinical practice; however, the main disadvantage is polymerization shrinkage, which could lead to microleakage, plaque accumulation, secondary caries, and hypersensitivity. For this reason, antimicrobial agents have been incorporated, such as light-curing quaternary ammonium methacrylate, fluoride ion-releasing glass fillers, pyrogallol, and nanoparticles of silver, calcium, and fluorinated graphene. In recent years, some of these have been shown to have good antimicrobial effectiveness and, in turn, do not interfere with adhesion in restorations. Thus, these antimicrobial adhesive systems could contribute to better long-term results. The best-performing nanoparticles were amorphous calcium phosphate and silver nanoparticles.